SISTEM INFORMASI PENGGAJIAN GURU DAN PEGAWAI DI SEKOLAH DASAR ADVENT 2 MEDAN BERBASIS WEB - Hutahaean, Artauli Meypia; Harianja, Eva Julia Gunawati; Purba, Eviyanti Novita (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2023)
The Design Information System of Payroll for Teachers and Employees in Medan Adventist 2 Elementary School is a research that has the goal of developing an information system that can be used efficiently to process the payroll process for teachers and employees of Medan Adventist 2 Elementary School. This information system is designed to facilitate the web-based payroll process which does not require a lot of time to process payroll, whereas previously the payroll process was done manually using a ledger which took quite a long time. The results of this study are a payroll information system for teachers and employees that can assist cashiers as admins in carrying out the payroll process and issuing salaries that will be received by teachers and employees accurately and systematically. This system is also equipped with a security feature that ensures that only the main admin, namely the cashier, has the authority to make payroll.